2016
DOI: 10.21013/jas.v4.n1.p2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Cracker (Fire Works) Injuries in a Tertiary Burn Care Centre

Abstract: Fireworks related burns are one of the causes of recurring incidences of burn injuries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…In the study above, it was found that men had a higher incidence rate of 28 (78%) than female 8 (22%). Higher incidence rates in male were also found in the study conducted by Gopalakrishnan et al (2016) with 78% male patients, Rajeswari et al (2016) with 66% male patients, Hatamabadi et al (2013) with 87% patients, Pilling and Govender (2016) 70.8% from all patients were male.…”
Section: Discussionmentioning
confidence: 52%
“…In the study above, it was found that men had a higher incidence rate of 28 (78%) than female 8 (22%). Higher incidence rates in male were also found in the study conducted by Gopalakrishnan et al (2016) with 78% male patients, Rajeswari et al (2016) with 66% male patients, Hatamabadi et al (2013) with 87% patients, Pilling and Govender (2016) 70.8% from all patients were male.…”
Section: Discussionmentioning
confidence: 52%
“…Soft tissue injuries directly affect the range of motion (ROM) during active flection after the skin folds above interphalangeal joints have healed and converted into scar tissue. 1 The scar tissue may adversely affect the ability to grab objects and may also affect other functions of the hand.…”
Section: Weighting Factorsmentioning
confidence: 99%
“…In the past, blast injuries were mainly caused by injuries during wars among both soldiers and civilians. 1 Nowadays, blast injuries still occur, mostly caused by low explosion such as firecrackers, with hands as the most frequently affected body part. 2 The incidence of the injury is seasonal, with a peak during holiday seasons and cultural events, such as during Eid Al-Fitr, Christmas, New Year, or during wedding ceremonies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations